Physical properties of modified Calcium Silicate-Based Cement (Csc) as root canal medicament / Walid Ali Almeeri - Walid Ali, Almeeri (2017)
Title: Physical properties of modified Calcium Silicate-Based Cement (CSC) As Root Canal Medicament. Objectives: To evaluate the physical properties of Calcium Silicate-Based Cement (CSC) by retarding its setting time after mixing with 2% Chlorhexidine gel (CHX) to be used as a root canal medicament. Methods: Three types of CSC were used in this study: white Portland cement (Aalborg, Malaysia), white ProRoot MTA (Tulsa, USA), and Biodentine (Septodont, France). CSCs were mixed with 2% CHX (n=8) with ratio of 2g powder:1g CHX. Calcium Hydroxide paste (Master-Dent, UAS) was used as a control in this study. The setting time, calcium ion release, pH of the water surrounding the specimens, film thickness and flowability of the CSC/CHX mixture (experimental cements) were assessed and measured following the standards of the ISO specification. Differences between materials and changes over time were compared with ANOVA and Tukey’s post-hoc tests at a significance level of 0.05. Results: CSC/CHX mixture did not set until 84 days. Calcium ion release of the experimental cements were significantly higher compared to control over the period of 14 days (P<0.001). The mean pH value were above 11.45 for all materials tested in this study over the period of 14 days, however, there was a statistical significant difference between them (P<0.001). The results also showed that there were no significant difference in film thickness of the experimental cements compared to control (P>0.05), however, the results of the flowability of the experimental cements was significantly higher than the control (P<0.05). Conclusions: The addition of 2% CHX to CSCs is retarding or inhibiting its setting reaction over a period of 84 days. The calcium ion release and flowability of this v CSC/CHX mixture cement were found to be better than Calcium Hydroxide. Therefore, this experimental cement has the potential to be used as an enhanced root canal medicament. Further research on this formulation (particularly biocompatibility and antibacterial properties) is needed.